Forced air warming during sedation in the cardiac catheterisation laboratory: a randomised controlled trial. Issue 8 (7th October 2017) - Conway, Aaron; Ersotelos, Suzanna; Sutherland, Joanna; Duff, Jed
Abstract : Objective: Forced air warming (FAW) during general anaesthesia is a safe and effective intervention used to reduce hypothermia. The objective of this study was to determine if FAW reduces hypothermia when used for procedures performed with sedation in the cardiac catheterisation laboratory. Methods: A parallel-group randomised controlled trial was conducted. Adults receiving sedation in a cardiac catheterisation laboratory at two sites were randomised to receive FAW or usual care, which involved passive warming with heated cotton blankets. Hypothermia, defined as a temperature less than 36°C measured with a sublingual digital thermometer after procedures, was the primary outcome. Other outcomes were postprocedure temperature, shivering, thermal comfort and major complications. Results: A total of 140 participants were randomised. Fewer participants who received FAW were hypothermic (39/70, 56% vs 48/69, 70%, difference 14%; adjusted RR 0.75, 95% CI=0.60 to 0.94), and body temperature was 0.3°C higher (95% CI=0.1 to 0.5, p=0.004). FAW increased thermal comfort (63/70, 90% vs51/69, 74% difference 16%, RR 1.21, 95% CI=1.04 to 1.42). The incidence of shivering was similar (3/69, 4% vs 0/71 0%, difference 4%, 95% CI=−1.1 to 9.8). One patient in the control group required reintervention for bleeding. No other major complications occurred. Conclusion: FAW reduced hypothermia and improved thermal comfort. The difference in temperature between groups was modest and less than that observed in previous studies where use of FAW decreased risk of surgical complications. Therefore, it should not be considered clinically significant. Trial registration number: ACTRN12616000013460.